Feed Intake and Growth as Affected by Inclusion of Detoxified Karanj (Pongamia glabra Vent) Seed Meal in Broiler Rabbit Rations - Giridhar, K.S.; Doss, R.G.; Reddy, B.S.V.; Prabhu, T.M.; Manju, G.U.; Nagabhushan, V. (Indian Journal of Animal Nutrition, 2018)
Thirty weaned New Zealand White broiler rabbits of similar age (6-7 weeks old) and body weight (747.68 g) were randomly allotted to 5 groups comprising of 6 (3 male and 3 female) rabbits in each group in order to study the effect of replacement of GN cake with solvent treated karanj (Pongamia glabra Vent) seed meal (SKSM) or alkali treated karanj seed meal (AKSM) on feed intake, average daily gain (ADG) and feed conversion ratio (FCR) for a period of 70 days. Five iso-nitrogenous and iso-caloric complete diets were formulated. The animals in group T1 (control) were given concentrate mixture containing 25% GN cake. In groups T2 and T3, GN cake was replaced by SKSM on N basis at 25 and 50% levels, respectively. Similarly, in groups T4 and T5, GN cake was replaced by AKSM on N basis at 25 and 50% levels, respectively. The average daily feed intake ranged from 65.27±1.92 (T3) to 71.56±1.81 (T2) g/h/d. The ADG ranged from 13.08±0.55 (T3) to 14.90±0.61 g (T1) and FCR from 5.00±0.15 (T1) to 5.41±0.11 (T2). These values were found to be similar in all the groups. Hence, solvent extracted or alkali treated karanj seed meal could replace GN cake up to 50% level in concentrate mixture containing 25% GN cake without any adverse effect on feed intake and growth of broiler rabbits.